RANCANG BANGUN APLIKASI PENCARIAN RUMAH IBADAH SEMUA AGAMA DI KOTA BATAM BERBASIS ANDROID - Zalukhu, Meiman Hasrat; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2023)
This journal presents the "House of Worship Locator," an Android application developed using Xamarin Form framework. Its purpose is to provide residents and visitors of Batam City with an efficient tool to find nearby houses of worship, such as mosques, churches, temples, and other religious sites. The app's implementation involved data collection, database creation, interface design, and rigorous testing. Utilizing GPS technology, it accurately pinpoints users' locations and displays nearby places of worship on an interactive map. Additionally, user-friendly features like search filters, reviews, and ratings enhance the user experience. The "House of Worship Locator" app demonstrates its efficacy through user testing, providing reliable information for users to conveniently find suitable religious venues in Batam City. By offering easy access to religious facilities, this application fosters inclusivity and religious tolerance within the community. It exemplifies the potential of mobile technology in promoting harmony among diverse religious communities in Batam City. The journal concludes by discussing future enhancements and its broader applicability in other urban areas. Through the "House of Worship Locator," Batam City embraces technology to support its citizens' religious needs effectively.